Differentially Expressed Mitochondrial Proteins in Human MCF7 Breast Cancer Cells Resistant to Paclitaxel - Daniel, Petr; Halada, Petr; Jelínek, Michael; Balušíková, Kamila; Kovář, Jan (International journal of molecular sciences, 2019)
Identification of novel proteins with changed expression in resistant cancer cells could be helpful in elucidation mechanisms involved in the development of acquired resistance to paclitaxel. In this study, we carried out a 2D-PAGE using the mitochondrial-enriched fraction from paclitaxel-resistant MCF7/PacR cells compared to original paclitaxel-sensitive MCF7 breast cancer cells. Differentially expressed proteins were identified employing mass spectrometry. We found that lysosomal cathepsin D and mitochondrial abhydrolase-domain containing protein 11 (ABHD11) had decreased expression in MCF7/PacR cells. On the other hand, mitochondrial carbamoyl-phosphate synthetase 1 (CPS1) and ATPase family AAA-domain containing protein 3A and 3B (ATAD3A, ATAD3B) were overexpressed in MCF7/PacR cells. Further, we showed that there was no difference in localization of CPS1 in MCF7 and MCF7/PacR cells. We demonstrated a significant increase in the number of CPS1 positive MCF7/PacR cells, using FACS analysis, compared to the number of CPS1 positive MCF7 cells. Silencing of CPS1 expression by specific siRNA had no significant effect on the resistance of MCF7/PacR cells to paclitaxel. To summarize, we identified several novel proteins of a mitochondrial fraction whose role in acquired resistance to paclitaxel in breast cancer cells should be further assessed.
Keywords: Drug Resistance, Neoplasm; carbamoyl-phosphate synthetase 1 (CPS1); Proteome; regulace genové exprese u nádorů; Proteomics; nádory prsu; breast cancer cells; proteomika; Gene Silencing; ATPase family AAA-domain containing protein 3A and 3B (ATAD3A, 3B); Carbamoyl-Phosphate Synthase (Ammonia); chemorezistence; two-dimensional electrophoresis; Paclitaxel; Humans; mitochondrie; mitochondriální proteiny; Female; tandemová hmotnostní spektrometrie; Mitochondria; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; paclitaxel resistance; MFC-7 buňky; frakcionace buněk; cathepsin D; mitochondria; Mitochondrial Proteins; Tandem Mass Spectrometry; karbamoylfosfátsynthasa (amoniak); ženské pohlaví; spektrometrie hmotnostní - ionizace laserem za účasti matrice; umlčování genů; Gene Expression Regulation, Neoplastic; abhydrolase-domain containing protein 11 (ABHD11); proteom; Cell Fractionation; MCF-7 Cells; lidé; paclitaxel; Breast Neoplasms